A two-dimensional material nanostructure and its preparation method and application
By combining electron beam exposure and maskless lithography technology, two-dimensional material nanostructures with nanogap structures were prepared, which solved the problem of difficult to prepare well-controlled nanostructures in the far infrared to terahertz band in the prior art, and achieved the coupling of strong local electromagnetic fields and the improvement of photonic device performance.
Patent Information
- Application Number
- CN202210620053.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-06-02
AI Technical Summary
The prior art is difficult to prepare well-controlled two-dimensional material nanostructures, especially in the medium- and far infrared to terahertz band, which limits the development of plasmon applications of graphene and other materials in this band.
Using a combination of electron beam exposure technology and maskless lithography technology, a nanogap structure with coupled plasmons with far infrared and even terahertz bands was prepared, and the Fermi energy level was regulated at the gate pressurization to regulate the coherent intensity and propagation length of the plasmon.
It realizes the control of a two-dimensional material nanostructure with a strong local electromagnetic field on the nanoscale, enhances the response of the plasmon in the terahertz band, and improves the electron emission performance and terahertz detection sensitivity of photonics devices.
Smart Images

Figure CN114955985B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of micro-nano photonics, and in particular to a two-dimensional material nanostructure and a preparation method and application thereof. Background Art
[0002] Terahertz waves refer to a section of the electromagnetic spectrum between terahertz waves and millimeter waves, with a frequency of 0.1 to 10 THz and a corresponding wavelength of 3000 to 30 μm. This frequency band covers the spectrum characteristics of many materials, including semiconductors, biomacromolecules, organisms, etc. Therefore, terahertz waves have broad application prospects in the fields of terahertz spectroscopy, terahertz imaging, security inspection, radar, and communication technology.
[0003] Plasmon effects based on the terahertz band are a development direction for expanding the above applications. Due to the inherent characteristics of inter-band electron transitions, intra-band electron scattering, and high electron concentration of traditional metal materials, their plasmon losses are high and the plasmon response is limited to the visible to near-infrared band. Therefore, the structure of traditional metal coupling from far-infrared to terahertz waves is often relatively large, making it difficult to integrate. Finding a new material is the key to solving the above problems.
[0004] Graphene is a hybridized Sp2 orbital with a honeycomb structure of a single atomic layer thickness and a band structure with Dirichlet zeros. It has metal-like properties in the mid-infrared to terahertz bands and is one of the preferred materials for studying plasmon effects in this band. A large number of studies have shown that the smaller the gap of the nanostructure, the stronger the localized plasmon field generated. However, the controllable preparation of planar nanogap structures that couple the mid-infrared and even terahertz bands limits the application of graphene. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a two-dimensional material nanostructure and a preparation method and application thereof. The present invention uses a method combining electron beam exposure technology and maskless lithography technology to controllably prepare a two-dimensional material nanostructure, which has a nanogap structure that couples plasmons in the mid- and far-infrared and even terahertz bands. In addition, in a photonic device prepared using the nanostructure, its Fermi level can be regulated by applying pressure to the gate, thereby regulating the coherence intensity and propagation length of the plasmon.
[0006] In a first aspect of the present invention, a method for preparing a two-dimensional material nanostructure coupled to electromagnetic waves is provided, the method comprising the following steps:
[0007] S1: transfer the 2D material to the substrate;
[0008] S2: Spin-coat positive electron beam glue and use electron beam exposure system to obtain the nanostructure of two-dimensional materials according to the designed layout;
[0009] S3: etching the two-dimensional material nanostructure in S2 using reactive ion beam and removing the positive electron beam glue in S2;
[0010] S4: Redesign the layout, spin-coat the positive photoresist and use the maskless lithography technology to perform overlay, and after the overlay is completed, expose the part outside the two-dimensional material nanostructure in S3 through development;
[0011] S5: etching the two-dimensional material exposed in S4 by oxygen plasma to remove the portion outside the nanostructure of the two-dimensional material.
[0012] According to the first aspect of the present invention, in some embodiments of the present invention, the dose of electron beam exposure in S2 is 200-400 μC / cm 2 .
[0013] In some preferred embodiments of the present invention, the electron beam current in S2 is 0.2-1 nA.
[0014] In the present invention, the dose and beam current of electron beam exposure have an important influence on the two-dimensional material nanostructure formed in the present invention. When the dose is too large, it will cause serious overexposure, and it is difficult to obtain a structure of smaller size. When the dose is too small, the electron beam cannot be exposed through, which will cause the phenomenon of unclean development during the development process. Although a beam current that is too large can speed up the exposure speed, it will also cause overexposure. If the beam current is too small, the exposure time will be increased, thereby increasing the price cost of the device preparation.
[0015] The existence of the light diffraction limit makes it difficult for the resolution of traditional photolithography to reach the submicron scale. The wavelength of electrons is the de Broglie wavelength, and electron beams can be used to prepare smaller structures. However, electron beam exposure has the defects of being expensive and slow in exposure speed, which limits the application of electron beams, especially its unsuitability for large-area exposure structures. In the present invention, a nanoscale structure is first prepared using an electron beam exposure system, and then the maskless photolithography overlay technique is combined to remove the parts outside the nanostructure, which saves costs and improves efficiency.
[0016] In some preferred embodiments of the present invention, the layout in S2 is drawn using KLayout software.
[0017] In some preferred embodiments of the present invention, the spin coating thickness of the positive electron beam glue in S2 is 100-500 nm.
[0018] In some preferred embodiments of the present invention, the spin coating speed of the positive electron beam gel in S2 is 3000-5000 rpm.
[0019] In some preferred embodiments of the present invention, after the positive electron beam glue is spin-coated in S2, it is baked at a temperature of 160-200°C to solidify the electron beam glue.
[0020] In some more preferred embodiments of the present invention, the baking time is 3 to 4 minutes.
[0021] In some preferred embodiments of the present invention, the positive electron beam glue includes 950PMMAA4 glue, PMMA A7 glue and ARP glue.
[0022] In some preferred embodiments of the present invention, the ARP glue comprises ARP 6200.09.
[0023] In some preferred embodiments of the present invention, after the exposure in S2 is completed, the obtained structure is immersed in methyl isobutyl ketone (MIBK) solution, isopropyl alcohol (IPA) and deionized water respectively, and then the two-dimensional material nanostructure is transferred to the substrate.
[0024] In some more preferred embodiments of the present invention, the soaking time in MIBK is 1 to 3 minutes.
[0025] In some more preferred embodiments of the present invention, the soaking time in IPA is 0.5 to 2 minutes.
[0026] In some more preferred embodiments of the present invention, the soaking time in deionized water is 0.5 to 2 minutes.
[0027] In some preferred embodiments of the present invention, the etching time in S3 is 8 to 15 seconds. The etching time cannot be too long. If the etching time is too long, the positive electron beam glue will be etched away or over-etching will occur.
[0028] In some preferred embodiments of the present invention, the oxygen flow rate during etching in S3 is 35-45 sccm.
[0029] In some preferred embodiments of the present invention, after the etching in S3 is completed, the obtained sample is immersed in acetone to remove the positive electron beam glue on the surface of the sample.
[0030] In some more preferred embodiments of the present invention, the soaking time is 2 to 12 hours.
[0031] In some preferred embodiments of the present invention, the layout in S4 is drawn based on the portion outside the two-dimensional material nanostructure.
[0032] In some preferred embodiments of the present invention, the positive photoresist described in S4 includes RZJ-390PG photoresist.
[0033] In some preferred embodiments of the present invention, the spin coating speed of the positive photoresist is 3000-5000 rpm.
[0034] In some preferred embodiments of the present invention, the spin coating thickness of the positive photoresist is 1.5-2.5 μm.
[0035] In some preferred embodiments of the present invention, the positive photoresist is baked at a temperature of 100-140° C. after spin coating.
[0036] In some more preferred embodiments of the present invention, the baking time is 1 to 3 minutes.
[0037] In some preferred embodiments of the present invention, the development time in S4 is 1 to 3 minutes.
[0038] In some preferred embodiments of the present invention, the developer used for development is a positive photosensitive developer.
[0039] In some preferred embodiments of the present invention, after etching in S5, the sample is immersed in acetone to remove the positive photoresist.
[0040] In some more preferred embodiments of the present invention, the soaking time is 1.5 to 3 hours.
[0041] In some preferred embodiments of the present invention, the two-dimensional material includes graphene, molybdenum oxide, black phosphorus, and metal oxides.
[0042] In some preferred embodiments of the present invention, the two-dimensional material is graphene, and the graphene can be single-layer graphene, double-layer graphene, or multi-layer graphene.
[0043] In some preferred embodiments of the present invention, the substrate comprises silicon, glass, or a flexible substrate.
[0044] In some more preferred embodiments of the present invention, the substrate is silicon.
[0045] In some more preferred embodiments of the present invention, the silicon includes high-resistance silicon and doped silicon.
[0046] In some preferred embodiments of the present invention, an insulating layer is coated on the substrate.
[0047] In some more preferred embodiments of the present invention, the insulating layer includes SiO2, HfO2, Al2O3, HBN, or ZrO2.
[0048] In some more preferred embodiments of the present invention, the insulating layer is an oxide layer.
[0049] In some preferred embodiments of the present invention, the electromagnetic waves include terahertz band electromagnetic waves and mid-infrared to far-infrared band electromagnetic waves.
[0050] The second aspect of the present invention provides a two-dimensional material nanostructure prepared by the preparation method described in the first aspect of the present invention.
[0051] According to the second aspect of the present invention, in some embodiments of the present invention, the two-dimensional material includes graphene, molybdenum oxide, black phosphorus, and metal oxide.
[0052] In some preferred embodiments of the present invention, the two-dimensional material is graphene, and the graphene can be single-layer graphene, double-layer graphene, or multi-layer graphene.
[0053] In some preferred embodiments of the present invention, the nanostructure has a gap structure.
[0054] In some more preferred embodiments of the present invention, the size of the gap is 100-500 nm.
[0055] In some more preferred embodiments of the present invention, the size of the gap is 100-400 nm.
[0056] The gap structure in the present invention can be a gap formed by a strip structure and a triangular structure, a gap formed by a square structure and a strip structure, or a gap formed by a strip structure and a circular structure. The shape of the gap formed in the present invention is not limited to the above description, and those skilled in the art can select it according to actual needs. Different layouts are designed according to different selected structures. When the size of the gap structure is 100 to 500 nm, the size of the gap designed in the layout is 10 to 200 nm.
[0057] Preferably, the gap structure in the present invention is formed by a nanostrip structure and a nanostrip structure with triangles distributed on the long side of the nanostrip, and the gap structure specifically refers to the distance between the tip of the triangle distributed on the nanostrip structure and the adjacent nanostrip, wherein the lengths of the two nanostrips are 150-250 μm, the widths of the two nanostrips are 5-6 μm, and a number of triangles are equidistantly distributed on the long side of one nanostrip, the base of the triangle is 2-4 μm, the height is 5-6 μm, the vertex angle relative to the base is 30°, and the degrees of the other two angles are the same, and the above structure is used as a repeating unit of the two-dimensional material nanostructure in the present invention. In the two-dimensional material nanostructure of the present invention, four of the above repeating units are arranged in parallel with the length direction of the nanostrip as a reference, that is, the two-dimensional material nanostructure in the present invention has a periodically repeated structure, and the distance between two adjacent repeating units is 8-20 μm.
[0058] The two-dimensional material nanostructure formed in the present invention can couple terahertz waves and is a structure with terahertz wave optical plasmon response.
[0059] The larger the size of the structure forming the nanogap, the longer the wavelength that can be coupled, and the smaller the size of the structure forming the nanogap, the shorter the wavelength that can be coupled. By adjusting the size of the structure forming the nanogap, a two-dimensional material nanostructure that couples electromagnetic waves in the mid-infrared to far-infrared band can be prepared.
[0060] A third aspect of the present invention provides a photonic device, wherein the photonic device comprises the two-dimensional material nanostructure described in the second aspect of the present invention.
[0061] According to the third aspect of the present invention, in some embodiments of the present invention, the photonic device further includes a substrate, an insulating layer, a cathode electrode and an anode electrode.
[0062] In some preferred embodiments of the present invention, the substrate comprises silicon, glass, or a flexible substrate.
[0063] In some more preferred embodiments of the present invention, the substrate is silicon.
[0064] In some more preferred embodiments of the present invention, the silicon includes high-resistance silicon and doped silicon.
[0065] In some preferred embodiments of the present invention, an insulating layer is coated on the substrate.
[0066] In some more preferred embodiments of the present invention, the insulating layer includes SiO2, HfO2, Al2O3, HBN, or ZrO2.
[0067] In some more preferred embodiments of the present invention, the insulating layer is an oxide layer.
[0068] In some preferred embodiments of the present invention, the insulating layer deposition method includes electron beam evaporation and thermal evaporation.
[0069] In some preferred embodiments of the present invention, when the selected substrate is not silicon, the photonic device further comprises a gate, wherein the gate is placed between the substrate and the insulating layer.
[0070] Since the silicon substrate is conductive, when the selected substrate is silicon, the insulating layer may be directly deposited on the silicon substrate without using a gate.
[0071] In some preferred embodiments of the present invention, the gate electrode comprises Au.
[0072] In some preferred embodiments of the present invention, the Au is connected to the substrate via an adhesion layer.
[0073] In some more preferred embodiments of the present invention, the adhesion layer includes a Ti layer and a Cr layer.
[0074] In some preferred embodiments of the present invention, the Cr layer or the Ti layer is deposited using an electron beam evaporation or a thermal evaporation process.
[0075] In some preferred embodiments of the present invention, the thickness of the Cr layer or the Ti layer is 5 to 15 nm.
[0076] In some preferred embodiments of the present invention, the Au layer is deposited using an electron beam evaporation or a thermal evaporation process.
[0077] In some preferred embodiments of the present invention, the thickness of the Au layer is 80-120 nm.
[0078] Applying voltage to the gate can regulate the Fermi level of the nanogap in the nanostructure of the photonic device, thereby adjusting the plasmon propagation length and plasmon interference intensity in the photonic device, which can significantly enhance the electron emission performance or the sensitivity of terahertz detection.
[0079] In some preferred embodiments of the present invention, the anode electrode and the cathode electrode include Au.
[0080] In some preferred embodiments of the present invention, the Au is connected to the insulating layer via an adhesion layer.
[0081] In some more preferred embodiments of the present invention, the adhesion layer includes a Ti layer and a Cr layer.
[0082] In some preferred embodiments of the present invention, the Cr layer or the Ti layer is deposited using an electron beam evaporation or a thermal evaporation process.
[0083] In some preferred embodiments of the present invention, the thickness of the Cr layer or the Ti layer is 5 to 15 nm.
[0084] In some preferred embodiments of the present invention, the Au layer is deposited using an electron beam evaporation or a thermal evaporation process.
[0085] In some preferred embodiments of the present invention, the thickness of the Au layer is 80-120 nm.
[0086] In some preferred embodiments of the present invention, a wet lift-off process is used to remove metal other than electrodes of the photonic device.
[0087] In some preferred embodiments of the present invention, annealing treatment is used to remove residual glue on the surface of the obtained two-dimensional material of the photonic device.
[0088] In some preferred embodiments of the present invention, the annealing is performed in a hydrogen atmosphere at a temperature of 350° C. and for a time of 1.5 h.
[0089] In some more preferred embodiments of the present invention, the flow rate of hydrogen is 400 sccm.
[0090] In the present invention, positive electron beam glue is used during electron beam exposure to first expose the nanostructure of the two-dimensional material, and then the nanostructure is patterned by reactive ion beam etching, the formed pattern is the same as the designed layout, and then the patterned structure is covered with positive electron beam glue, the part outside the structure is exposed, and then the part outside the nanostructure of the two-dimensional material is completely removed by an oxygen plasma cleaner. Similarly, a maskless overlay system is used to prepare a patterned electrode for the above-mentioned two-dimensional material nanostructure, a Ti layer or a Cr layer is deposited on the patterned electrode as a bonding layer, an Au layer is deposited as a cathode and an anode, and a wet stripping process is used to remove the metal outside the electrode.
[0091] In the electron beam exposure process, the present invention uses positive electron beam glue PMMA. Although the use of positive electron beam glue adds a maskless overlay process to the subsequent process, positive electron beam glue PMMA has the advantages of high precision and easy removal, and can prepare a gap structure with a size close to 100nm.
[0092] Traditional negative electron beam colloids can greatly simplify the preparation process. HSQ is a commonly used negative electron beam colloid with high resolution, but HSQ degumming requires hydrofluoric acid, which is not applicable to samples with silicon oxide substrates. Other negative electron beam colloids (such as SU-8, MaN, etc.) have low resolution and are not easy to prepare small structures.
[0093] The beneficial effects of the present invention are:
[0094] The present invention can controllably prepare a planar coupled plasmon two-dimensional material nanostructure through an electron beam exposure system and a maskless lithography system. A gap with a size of 100 to 500 nm is formed in the prepared nanostructure. The smaller the gap, the stronger the local electromagnetic field generated by the nanostructure coupling the incident wave, which is beneficial to the application of the structure in subsequent enhanced electron emission and photoelectric detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0095] Figure 1 This is a scanning electron microscope image of the repeating unit in the nanostructure of graphene material;
[0096] Figure 2 The finite element method FDTD is used to calculate the dependence of the electric field enhancement of the graphene nanostructure in the embodiment of the present invention on the incident electromagnetic wave and the near-field profile of the electric field distribution at a wavelength of 1.2 THz;
[0097] Figure 3 is a scanning electron microscope image of the graphene nanostructure prepared in Example 1;
[0098] Figure 4 This is the process flow of the graphene nanostructure photonic device in Example 4;
[0099] Figure 5 This is a scanning electron microscope image of the graphene nanostructure photonic device in Example 4. DETAILED DESCRIPTION
[0100] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.
[0101] In the present invention, the FDTD Solutions software is first used to design a layout of a nanostructure capable of coupling terahertz waves. The nanogap in the nanostructure is composed of nanostrips and triangular tips. The triangular nanotip in the structure can have a strong electric field enhancement characteristic in a wide band (0.1-3THz), wherein the enhancement is strongest at a wavelength of about 1.2THz. Ordinary photolithography has the advantages of short exposure time and easy large-area photolithography. However, ordinary photolithography uses an ultraviolet light source. Due to the existence of the ultraviolet light diffraction limit, the accuracy of ultraviolet light is about half a wavelength, making it difficult for ordinary photolithography to reach the submicron scale. Electrons have a de Broglie wavelength, so electron beam exposure has a high accuracy, and the accuracy can reach nanometer scale. However, electron beam exposure has the defects of long time, high price and being unfavorable for large-area exposure. Therefore, in the embodiment of the present invention, an electron beam exposure system and a maskless photolithography system are combined, and a nanostructure of planar coupled plasmons can be controlled to be prepared, forming a nanogap with a size of 100nm.
[0102] The graphene nanostructure photonic device in the embodiment of the present invention includes a substrate, an insulating layer deposited on the substrate, a graphene nanostructure, a cathode electrode and an anode electrode.
[0103] The gap structure in the embodiment of the present invention is formed by a nanostrip structure and a nanostrip structure with triangles distributed on the long side. The gap structure specifically refers to the distance between the tip of the triangle distributed on the nanostrip structure and the adjacent nanostrip, wherein the lengths of the two nanostrips are both 80 μm, the widths of the two nanostrips are both 5.6 μm, a number of triangles are equidistantly distributed on the long side of one nanostrip, the distance between two adjacent triangles is 2 μm, the height of the triangle is 5.6 μm, the vertex angle relative to the base is 30°, and the degrees of the other two angles are the same. The above structure is a repeating unit in the two-dimensional material nanostructure in the embodiment of the present invention, and the scanning electron microscope image of the repeating unit is as follows Figure 1 As shown in the figure, it can be seen that the gap size between the graphene nanostrip and the triangular tip in the repeating unit is about 100nm. According to the coupling characteristics of the plasmon characteristics, the smaller the gap between the graphene strip and the triangular tip, the stronger the local electromagnetic field generated by the graphene nanostructure coupling the incident electromagnetic wave. Therefore, the nanoscale gap in the graphene nanostructure in the embodiment of the present invention can be ultra-strongly coupled to the terahertz band electromagnetic waves and the mid-infrared to far-infrared band electromagnetic waves Plasmons are beneficial to its subsequent application in enhanced electron emission and photoelectric detection. In the two-dimensional material nanostructure in the embodiment of the present invention, with the length direction of the nanostrip as a reference, four of the above-mentioned repeating units are arranged in parallel, that is, the two-dimensional material nanostructure in the embodiment of the present invention has a periodically repeated structure, and the distance between two adjacent repeating units is 5 to 20μm.
[0104] Those skilled in the art may also select other numbers of repeating units as needed, and those skilled in the art may also select the number of triangles on the nanoribbon as needed.
[0105] The graphene used in this embodiment is a single-layer graphene.
[0106] The cathode electrode and the anode electrode in this embodiment are Au, wherein the Ti layer serves as an adhesion layer connecting the cathode electrode and the anode electrode with the insulating layer.
[0107] The substrate used in this embodiment is silicon with a thickness of 500 μm, and the deposited insulating layer is SiO 2 with a thickness of 300 nm.
[0108] The finite element method FDTD is used to calculate the dependence of the electric field enhancement of the graphene nanostructure in the embodiment of the present invention on the incident electromagnetic wave. The results are as follows: Figure 2 As shown in a, Figure 2 The x-axis in a represents the wavelength of the excitation wave, and the y-axis represents the ratio of the generated local electric field to the incident light field, where the electric field component of the incident light field is 1. Figure 2It can be seen from a that in a wide band of 0.1 to 3 THz, the electric field generated by the local field of the plasmon at the tip of the triangle is greatly enhanced, and the field enhancement reaches the strongest at a wavelength of about 1.2 THz. The near-field profile of the electric field distribution at a wavelength of 1.2 THz is given, as shown in Figure 2 As shown in b, from Figure 2 In b, it can be seen that there is a strong field enhancement between the triangle tip and the graphene strip opposite to it.
[0109] In an embodiment of the present invention, a method for preparing a graphene nanostructure photonic device is provided. First, a single layer of graphene is transferred to a silicon substrate connected to a SiO2 insulating layer, and the graphene material is patterned by electron beam exposure and reactive ion beam etching, and then the patterned graphene is protected by a conventional maskless lithography overlay process, and the graphene on other parts of the substrate is removed by a plasma etching process. Finally, the graphene structure is patterned by a conventional maskless lithography process, and a patterned electrode is prepared for the above-mentioned graphene two-dimensional material nanostructure by using a maskless overlay system, a Ti layer is deposited on the patterned electrode as a bonding layer, an Au layer is deposited as a cathode electrode and an anode electrode (collectively referred to as an Au electrode), and the metal outside the electrode is removed by a wet stripping process.
[0110] Example 1
[0111] The preparation method of the graphene nanostructure in Example 1 is:
[0112] S1: Place the silicon substrate connected with the SiO2 insulating layer in acetone, ethanol and water for 15 minutes of ultrasound respectively, take it out and blow it dry with a nitrogen gun;
[0113] S2: Transferring the single-layer graphene to the substrate cleaned in S1 by wet transfer;
[0114] S3: Spin-coat the graphene surface in S2 with positive electron beam gel 950PMMA A4 to form an electron beam resist layer with a thickness of about 200 nm. The electron beam gel spin coating speed is 4000 rpm. The graphene nanostructure is obtained by using an electron beam exposure system according to the designed layout. The electron beam dose is 280 μC / cm 2 , the electron beam current size is 0.3nA.
[0115] S4: Reactive ion beam etching of the graphene nanostructure in S3 was performed using oxygen as the process gas and the pressure in the chamber was 7.5×10 -9 mPa, the oxygen flow rate is 40scsm, the RF power is 50W, and the etching time is 10s. After etching, the obtained structure is immersed in acetone for 2h to remove the electron beam glue;
[0116] S5: Redesign the layout and spin-coat the positive photoresist RZJ-390PG to form a 2.5μm thick photoresist layer to protect the graphene nanostructure in S4. The spin coating speed of RZJ-390PG is 4000rpm. The maskless lithography technology is used to overlay to remove the parts outside the graphene nanostructure. After the overlay is completed, the two-dimensional material outside the nanostructure in S3 is exposed through development. The development exposure time is 10s. The model of the lithography machine used is uPG501.
[0117] S6: etching the graphene outside the graphene nanostructure exposed in S5 using oxygen plasma, and removing the photoresist RZJ-390PG.
[0118] The operation steps of transferring graphene to the substrate in S1 are as follows: first, place the substrate in acetone, ethanol and deionized water and ultrasonicate for 15 minutes respectively. Cut the graphene with filter paper into a suitable size, slowly drip deionized water onto the surface of the graphene to moisten it, put it into deionized water after moistening, and remove the filter paper. At this time, the graphene floats on the water surface. Then use a flexible substrate to pick up the graphene from the bottom of the graphene, and then put the graphene back into the water. At this time, there are bubbles on the flexible substrate. Repeat the above action several times until there are no bubbles on the flexible substrate, indicating that the bubbles on the graphene have been removed. Then tilt the flexible substrate at a certain angle to move the graphene to the above-mentioned cleaned substrate. Finally, use a nitrogen gun to blow out the water film between the graphene and the substrate, and place it in a clean and dry place to dry for 24 hours, so that the adhesion between the graphene and the substrate is better.
[0119] The layout of S3 in the embodiment of the present invention is drawn using KLayout software, and the layout is converted into a PSF file using Beamer software. The layout consists of a strip structure and a strip structure with triangles distributed on the long side of the strip, wherein the length of the strip is 80 μm, the width of the strip is 5.6 μm, the height of the triangle is 5.6 μm, the vertex angle relative to the base of the triangle is 30°, the degrees of the other two angles are the same, the distance between two adjacent triangles is 2 μm, and the distance between the tip of the triangle and the adjacent strip is 20 nm.
[0120] During the electron beam exposure process in S3, the step length of the electron beam spot movement is 2nm, and the model of the electron beam exposure system is Raith EBPG 5000plus. During the electron beam exposure process, if the exposure dose is too large, it will cause overexposure, and it will be difficult to prepare a gap structure with a distance of 100nm between the tip of the graphene triangle and the strip. If the dose is too small, it is easy to cause underexposure, making it impossible to completely remove the positive electron beam glue in the exposed area during the development process, affecting the subsequent etching process. In addition, the beam size is also an important parameter. Although a beam current that is too large can speed up the exposure speed, it will also cause overexposure. If the beam current is too small, the exposure time will be increased, thereby increasing the price cost.
[0121] The layout in S5 is designed according to the shape other than the layout in S3.
[0122] In S6, since PMMA reacts with oxygen plasma, if the etching time is too long, the PMMA anti-agent layer will be etched away, causing the graphene nanostructure on the substrate to be etched away. If the etching time is too short, the graphene in the graphene nanostructure part cannot be etched cleanly, thus affecting subsequent tests.
[0123] Figure 3 The dashed line frame is a scanning electron microscope image of the graphene nanostructure prepared in Example 1 of the present invention. Figure 3 It can be seen that by using 950PMMA A4 as electron beam glue, a graphene nanostructure can be prepared after electron beam exposure and subsequent oxygen plasma etching and degumming processes. There is a gap between the graphene nanoribbons and the triangular tip in the graphene nanostructure, and the graphene nanostructure has periodically repeated structural units.
[0124] Example 2
[0125] The method for preparing the graphene nanostructure in Example 2 is the same as that in Example 1, except that the positive electron beam glue used in S3 in Example 2 is PMMA A7.
[0126] Example 3
[0127] The preparation method of the graphene nanostructure in Example 3 is the same as that in Example 1, except that the positive electron beam glue used in S3 of Example 3 is ARP 6200.09, and after the etching in S4 is completed, the obtained structure is immersed in acetone for 10 hours to remove the electron beam glue.
[0128] Example 4
[0129] Fabrication of graphene nanostructured photonic devices:
[0130] In Example 1, a graphene nanostructure is obtained. A positive photoresist RZJ-390PG is spin-coated on the surface of the structure obtained in S6 of Example 1 to form a 2.5 μm thick photoresist layer to protect the graphene nanostructure in S6. The spin coating speed of RZJ-390PG is 4000 rpm. Then, the electrode layout is redesigned. The electrode layout is a square with a side length of 400 to 500 μm. The designed electrode layout is patterned using the designed layout and the maskless photolithography technology in S5, and developed. After the development is completed, the electrode layout is patterned using Electron beam evaporation is used to deposit 5nm thick Ti as an adhesion layer on the above structure, and then 100nm thick Au is deposited as an electrode, wherein the cathode electrode is Au and the anode electrode is also Au, and the two electrodes are respectively connected to the nanostrips without triangles and the nanostrips with triangles in the graphene nanostructure, and the above two electrodes are pressed on the graphene to form an ohmic contact. In order to facilitate the cathode to emit electrons, a low voltage is applied to the electrode connected to the nanostrips with triangles, and a high voltage is applied to the electrode connected to the nanostrips without triangles. Finally, a wet stripping process is used to remove the metal other than the electrode in the above structure to obtain a photonic device of a graphene nanostructure, and the obtained device is annealed in a tubular furnace to remove the residual glue on the surface of the graphene nanostructure, wherein hydrogen is introduced into the tubular furnace, the flow rate of hydrogen is 400sccm, the annealing temperature is 350°C, and the annealing time is 1.5h. Regarding the size of the electrode, those skilled in the art can also choose different sizes and shapes as needed. The specific process flow of graphene nanostructured photonic devices is as follows: Figure 4 The scanning electron microscope image of the prepared photonic device is shown in Figure 5 As shown, Figure 5 Only a portion of the electrode is shown.
[0131] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a two-dimensional material nanostructure coupled to electromagnetic waves, characterized in that: The method comprises the following steps: S1: transfer the 2D material to the substrate; S2: Spin-coat positive electron beam glue and use electron beam exposure system to obtain the nanostructure of two-dimensional materials according to the designed layout; S3: etching the two-dimensional material nanostructure in S2 using reactive ion beam and removing the positive electron beam glue in S2; S4: Redesign the layout, spin-coat the positive photoresist and use the maskless lithography technology to perform overlay, and after the overlay is completed, expose the part outside the two-dimensional material nanostructure in S3 through development; S5: etching the two-dimensional material exposed in S4 by oxygen plasma to remove the portion outside the nanostructure of the two-dimensional material; The dose of electron beam exposure in S2 is 200~400 μC / cm 2 , the electron beam current is 0.2~1 nA.
2. The method according to claim 1, characterized in that The positive electron beam glue described in S2 includes 950 PMMA A4 glue, PMMA A7 glue and ARP 6200.09 glue.
3. The method according to claim 1, characterized in that The spin coating thickness of the positive electron beam glue described in S2 is 100~500 nm.
4. The method according to claim 1, characterized in that: The positive photoresist described in S4 includes RZJ-390 PG photoresist, wherein the spin coating thickness of RZJ-390 PG photoresist is 1.5~2.5 μm.
5. The method according to claim 1, characterized in that The two-dimensional material includes graphene, molybdenum oxide, black phosphorus or metal oxide.
6. The method according to claim 1, characterized in that The electromagnetic waves include terahertz band electromagnetic waves or mid-infrared to far-infrared band electromagnetic waves.
7. The two-dimensional material nanostructure prepared by the method according to any one of claims 1 to 6, characterized in that: The nanostructure has a gap structure, and the size of the gap is 100-500 nm.
8. A photonic device, characterized in that: The photonic device comprises the two-dimensional material nanostructure as claimed in claim 7.
9. The photonic device according to claim 8, characterized in that: The photonic device also includes a substrate, an insulating layer, a gate, a cathode electrode and an anode electrode.
10. Use of the photonic device according to claim 8 or 9 in electromagnetic wave enhanced electron emission and photoelectric detection.
Citation Information
Patent Citations
Production method of two-dimension photon crystal with annular hole array structure
CN101470347A
Method for producing nano-dimension metal structure overlapped by metal membrane in large area
CN101470355A